A Review of Fault Diagnosis in Dynamic Control Systems - สายใจ, เจษฎา (Srinakharinwirot University Engineering Journal, 2018)
This paper aims to review the techniques for fault diagnosis in dynamic control systems. The basic concept including definition and type of fault is firstly addressed. Following by the current fault diagnosis techniques published in the literatures such as hardware redundancy, model-based, data-driven and signal analysis approach. Discussion and future trend of the fault diagnosis are also presented. This information can be used for improving the fault diagnostic in dynamic control system.